ANALISIS KURIKULUM MADRASAH TSANAWIYAH DAN MADRASAH ALIYAH PESANTREN MODERN UNGGULAN TERPADU DARUL MURSYID SIDAPDAP SIMANOSOR KECAMATAN SAIPAR DOLOK HOLE KABUPATEN TAPANULI SELATAN - Husni Mubarok (Jurnal Penelitian Ilmu Pendidikan Indonesia, 2023)
This research is studying about Islamic boarding school in general both classic (salafi) or modern (Khalafi) adopt the curriculum of classical texts or studying the kitab kuning as their characteristic. DarulMursyid Islamic boarding school at the standing start aiming for tafaqquh fiddin that changing the goal of becoming a science Islamic boarding school. This research used field research approach with the type of research is qualitative.The determination of informants of this research used purposive sampling. Data collection techniques used consist of observation, interviews, and documentation. Data analysis using the concept of Miles and Huberman namely data reduction, data display and conclusion. The results of the research show that: 1.the transformation of Islamic junior high school and Islamic senior high school curriculum of Darul Mursyid Islamic boarding school is the result of the questionnaire evaluation conducted to every student who wants to continue study after graduating from Darul Mursyid and the interest students showed to continue their studies to reputable-university with general basic in java region. 2.the percentage of General and Religious knowledge are as follows: the percentage for General knowledge is 75% dan for Religious knowledge is 25% both of Islamic Junior High School and at Islamic Senior High School